∫exx2 + 1x + 12dx is equal to
exx + 1 + C
- exx + 1 + C
exx - 1x + 1 + C
exx + 1x - 1 + C
∫x + 1x1 + xexdx is equal to
log1 + xexxex + C
logxex1 + xex + C
log1 + xex + C
∫fxg'x - f'xgxfxgxloggx - logfxdx is equal to
loggxfx + C
12loggxfx2 + C
gxfxloggxfx + C
loggxfx - gxfx + C
∫0π4sinx + cosx3 + sin2xdx = ?
12log3
log2
log(3)
14log3
∫- 111 + x + x2 - 1 - x + x21 + x + x2 + 1 - x + x2dx = ?
3π2
π2
0
- 1
If ∫x3e5xdx = e5x54fx + C,then fx = ?
x35 - 3x252 + 6x53 - 654
5x3 - 52x2 + 53x - 6
53x3 - 15x2 + 30x - 6
53x3 - 75x2 + 30x - 6
∫xx2 + 2x + 22dx = ?
x2 + 2x2 + 2x + 2 - 12tan-1x - 1 + C
x2 - 24x2 + 2x + 2 - 12tan-1x + 1 + C
x2 + 22x2 + 2x + 2 - 12tan-1x + 1 + C
2x - 1x2 + 2x + 2 + 12tan-1x + 1 + C
If ∫loga2 + x2dx = hx + C, then hx = ?
xloga2 + x2 + 2tan-1xa
x2loga2 + x2 + x + atan-1xa
xloga2 + x2 - 2x + 2atan-1xa
x2loga2 + x2 + 2x - a2tan-1xa
C.
Let I = loga2 + x2dxBy using integration by parts, we get= loga2 + x2∫dx - ∫d loga2 + x2dx∫dxdx + C= xloga2 + x2 - ∫2xx2 + a2dx + C= xloga2 + x2 - 2x + 2a2atan-1xa + C= xloga2 + x2 - 2x + 2atan-1xa + C∴ hx = xloga2 + x2 - 2x + 2atan-1xa
For x > 0, if ∫logx5dx = ?xAlogx5 + Blogx4+ Clogx3 + Dlogx2 + Elogx + F + Constant, thenA + B + C + D + E + F = ?
- 44
- 42
- 40
- 36
By the definition of the definite integral, the value of limn→∞1n2 - 1 + 1n2 - 22 + ... 1n2 - n - 12 is equal to
π
π4
π6